Sleep patterns in paediatric patients with atopic dermatitis at Chris Hani Baragwanath hospital, Johannesburg, South Africa - Rouhani-N, Mary M (My University, 2017)
Introduction: Atopic Dermatitis (AD) is a chronic relapsing inflammatory skin condition affecting 5-20% of children under 11 years of age, characterised by intense pruritus, redness and discomfort. Research suggests that AD has been shown in quality of life assessments to be rated among the worst in term of its effect on sleep. There is no research on the effects of sleep loss on the natural history and time course of skin disorders either, especially in South Africa. Aims: The objectives of this study were: 1. to describe the various sleep disturbances associated with AD in children up to and including 12 years of age and 2. to compare the characteristics of children with sleep problems to those without sleep problems in AD Patients and Methods: This was a prospective observational / descriptive hospital based study conducted at the paediatric dermatology outpatient department at Chris Hani Baragwanath Academic Hospital (CHBAH). Questionnaire technique was used consisting of the children’s sleep habits questionnaire (CSHQ), a useful parent-reported instrument validated to identify both behaviourally based and medically based sleep problems in 4-12 years old school age children. Results: The prevalence of sleep problems in paediatric patients with AD was found to be 61.3%. There was no significant difference between males and females. Snoring as well as apnoea and snorting were significantly different in the rhinitis versus non-rhinitis group. The overall sleep disturbance rate was significantly different in those with rhinitis versus those without. Conclusions: While Atopic Dermatitis is often regarded by health professionals as a minor problem, in this study, 61.3% of children with AD have disturbed sleep.
Faculty of Health Sciences, WITS University, as partial fulfillment for the requirements of the degree of Master of Medicine in Dermatology Johannesburg 2017
Keywords: Atopic Dermatitis Paediatric